Pengelolaan Sampah Organik di Desa Wisata Air Hitam sebagai Upaya Implementasi Green Economy, Kelurahan Kereng Bangkirai: Management of Organic Waste in the Air Hitam Tourism Village as an Effort to Implement a Green Economy, Kereng Bangkirai District - Wulandari, Meyta; Kurniati, Ety; Samudra, Agung; Ngazizah, Febri Nur; Hasanah, Rizka; Tuju, Fandi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Ecosystems in Central Kalimantan are generally dominated by peat swamps, including Kereng Bangkirai Village, Sebangau District. Ecotourism is responsible for improving community welfare but still prioritizing the environmental preservation of natural areas found in tourist locations. Education on waste management in the community is still lacking, reflected in the lack of sorting when disposing of household waste to the landfill and residents' habit of burning environmental waste in the form of leaves or dry grass. The Riswandi Farm farmer group uses the results of cutting grass in the Kereng Bangkirai area to be used as compost. However, the limitations of the grass-cutting tools used are an obstacle in producing compost. So it is necessary to apply shredding machine technology to overcome the problem of the amount of organic compost production and produce derivative fertilizer products in other forms.